Slice Co : Multi Meat Slicer / Edzzry Indrawan Faizal Edzuan ...[et al.] - Faizal Edzuan, Edzzry Indrawan; Abdul Muttalib, Ainul Mustaqim; Azrin, Aina Balqis; Mohamed Amir Khan, Azrief Raziq Khan; Ahmad, Azam Shah; Mohd Shah, Amierul Hakim (2016)
Slice Co. is a small company that produce and sell meat slicer machine at an affordable price. The company is established to encounter the problem faced by the public to get fresh minced meat